Post-traumatic growth and its influencing factors among Chinese women diagnosed with gynecological cancer: A cross-sectional study. (April 2021) - Zhou, Li-Hua; Hong, Jing-Fang; Qin, Ru-Meng; Henricson, Maria; Stenmarker, Margaretha; Browall, Maria; Enskär, Karin
Abstract: Purpose: The experience of cancer could lead to positive psychological changes following the struggle with diagnosis and treatment. Understanding post-traumatic growth and its influencing factors in women affected by gynecological cancer is essential to enhance their possibility of achieving positive changes. The purpose of this study was to describe the post-traumatic growth level and explore the influencing factors of post-traumatic growth in Chinese women diagnosed with gynecological cancer. Method: A cross-sectional survey with a convenience sampling method was employed to collect data using the Post-traumatic Growth Inventory (PTGI), Distress Disclosure Index (DDI), Medical Coping Modes Questionnaire (MCMQ), and Multidimensional Scale of Perceived Social Support (MSPSS). The questionnaires were administered to 344 participants recruited from two hospitals in Hefei City, the capital of Anhui Province in China, between March 2018 and March 2019. All statistical analyses were performed using nonparametric tests. The Mann-Whitney U Test was used to distinguish the intergroup differences. Correlations were evaluated with Spearman rank correlation coefficients. Results: Total score for PTGI was 56.5 (range 48.0–68.0). The subscale with the highest centesimal score in the PTGI was appreciation of life and the lowest was spiritual change. The top five items with the highest scores of PTGI belonged to appreciating life, personal strength, and relating to others. Self-disclosure, confrontation, avoidance, acceptance-resignation, perceived social support, education level, cancer type and the place they lived had significant influence on post-traumatic growth. Conclusions: The findings indicate that women who have high levels of perceived social support, confrontation, avoidance, self-disclosure and education level tend to experience more post-traumatic growth, while, conversely, high levels of acceptance-resignation have a negative influence on promoting post-traumatic growth. These meaningful findings propose new perspectives for promoting post-traumatic growth in Chinese women diagnosed with gynecological cancer. Highlights: Self-disclosure has a positive influence on post-traumatic growth. Confrontation and avoidance have a positive influence on post-traumatic growth. Acceptance-resignation has a negative influence on post-traumatic growth. Perceived social support has a positive influence on post-traumatic growth. Women diagnosed with endometrial cancer or ovarian cancer had lower post-traumatic growth levels.